OPTIMALISASI INFRASTRUKTUR HIJAU PERKOTAAN MENGGUNAKAN GREEN ROOF, RAIN GARDEN, DAN PERMEABLE PAVEMENT DENGAN MODEL SWMM - Nurhamidah (Universitas Andalas, 2026)
Urban development in Padang City has increased impervious surface areas, reduced infiltration capacity, and increased surface runoff. This condition often overloads the existing drainage system, leading to inundation during high rainfall events. This research was conducted in the Pelangi Indah Residential Area, Korong Gadang Village, Kuranji District, Padang City, aiming to analyze and optimize the application of green infrastructure in the form of green roofs, rain gardens, and permeable pavements using the EPA SWMM model. The data used consisted of primary data obtained through field surveys, including drainage dimensions and elevations measured with water-pass instruments, as well as secondary data such as rainfall data from NASA's Giovanni GPM IMERG, land-use data, and soil parameter data. Simulations were conducted under existing conditions and in several Low Impact Development (LID) scenarios to evaluate the effectiveness of each green infrastructure technology in reducing runoff and increasing infiltration. The simulation results showed that the existing condition of the study area still produced relatively high runoff due to the dominance of built-up areas and the limited infiltration zones. After implementing the combination of green roofs, rain gardens, and permeable pavements, there was a decrease in runoff volume, a reduction in peak discharge, and an increase in rainwater infiltration into the soil. The combined scenario of the three LID technologies showed better hydrological performance than existing conditions. This study is expected to serve as a reference for sustainable urban drainage system development based on green infrastructure in Padang City and other urban areas.